Characterization of buried interfaces using Ga Kα hard X-ray photoelectron spectroscopy (HAXPES). (9th May 2022) - Spencer, B. F.; Church, S. A.; Thompson, P.; Cant, D. J. H.; Maniyarasu, S.; Theodosiou, A.; Jones, A. N.; Kappers, M. J.; Binks, D. J.; Oliver, R. A.; Higgins, J.; Thomas, A. G.; et al.
Abstract : HAXPES enables the detection of buried interfaces with an increased photo electron sampling depth. Abstract : The extension of X-ray photoelectron spectroscopy (XPS) to measure layers and interfaces below the uppermost surface requires higher X-ray energies and electron energy analysers capable of measuring higher electron kinetic energies. This has been enabled at synchrotron radiation facilities and by using lab-based instruments which are now available with sufficient sensitivity for measurements to be performed on reasonable timescales. Here, we detail measurements on buried interfaces using a Ga Kα (9.25 keV) metal jet X-ray source and an EW4000 energy analyser (ScientaOmicron GmbH) in the Henry Royce Institute at the University of Manchester. Development of the technique has required the calculation of relative sensitivity factors (RSFs) to enable quantification analogous to Al Kα XPS, and here we provide further substantiation of the Ga Kα RSF library. Examples of buried interfaces include layers of memory and energy materials below top electrode layers, semiconductor heterostructures, ions implanted in graphite, oxide layers at metallic surfaces, and core–shell nanoparticles. The use of an angle-resolved mode enables depth profiling from the surface into the bulk, and is complemented with surface-sensitive XPS. Inelastic background modelling allows the extraction of information about buried layers at depths up to 20 times the photoelectron inelastic mean free path.